Um imaginário memorial da humanidade : mitocrítica, performance e dança contemporânea - Luis Roberto Abreu Corrêa (2014)
It´s proposed the ethnography of the contemporary dance spectacle brancoemMim, creation of the Companhia de Dança Palácio das Artes. The work of art is based on site specific proposal, where space influence artistic creation. The analysis is divided into two levels: the first was treated to an interpretation of the spectacle through the Mitocrítica of Gilbert Durand, and the focus of the second level was its performance, in particular the relationship between expression and experience, following the theory of Victor Turner. Thus, structure and practice are contemplated. The objective of the research was the realization of the interpretation of the spectacle through the hermeneutics of the two authors, and the basis on which the thesis was woven were the interviews of the artists and the public.